KEY DRIVER OF KNOWLEDGE WORKER PRODUCTIVITY: THE ROLES OF PERSONAL KNOWLEDGE MANAGEMENT 2.0 AND DIGITAL COMPETENCE - Prakasa, Yudha; Astuti, Endang Siti; Damayanti, Alifah (FIA UB, 2021)
This research aims to know and explain whether there is a simultaneous influence between Personal Knowledge Management 2.0 (X1) and Digital Competence (X2) on Knowledge Worker Productivity (Y), and the partial influence between Personal Knowledge Management 2.0 (X1) on Knowledge Worker Productivity (Y) and Digital Competence (X2) on Knowledge Worker Productivity (Y). This research is quantitative research and the research type is explanatory research. The number of samples in this study was 50 persons of employees in PT Alpha Teknologi Indonesia Malang. The sampling technique used is census sampling. Sources of data in this study were obtained from the primary data by spreading questionnaires to the respondents and secondary data derived from the documentation. The measurement scale used in this reseach is Likert scale. This research using descriptive statistics analysis and multiple linier regression analysis with a classic assumption test. Data on this research is processed using SPSS 23 for Windows.